Filipino Collaboration and Atrocities in the Japanese-Occupied Philippines and Their Unjust Judicial Consequences: A Case Study of Sagay, Negros Occidental - Ara, Satoshi; Ohtsuki (Archīum Ateneo, 2023)
Philippine historiography has long ignored the wartime collaboration issues of rural landed elites during the Japanese occupation, some of whom were involved in violent acts. It also has not yet thoroughly examined the unjust judicial consequences of the postwar treason trials under the People’s Court, which acquitted most of the accused rural elites and convicted many poor landless peasants who faced the same charges. Thisarticle examines the case of Sagay, Negros Occidental, to clarify how the landed rich used the poor in collaborating with the Japanese to protect their sugar interests and how the social division among Negrenses deepened after the war. KEYWORDS: NEGROS OCCIDENTAL • WARTIME VIOLENCE • SUGAR BARONS • JUDICIARY • SOCIAL DIVISION